Financial Use of Technology for Agriculture Business Perpetrators in Mojolaban - Ferina Indah Sari; Sri Padmantyo (Proceedings Series on Social Sciences & Humanities, 2024)
Facilitating transactions in the agricultural sector is crucial in achieving independent farming. In this article we will discuss the activities of community service through socialization and training using the ICARE method (Introduction, Connection, Application, Reflection, Extend). The aim of this dedication is to provide an understanding of the use and use of financial technology in the agricultural sector in order to expand the business ecosystem and facilitate transactions. Fintech has the advantage of providing 24-hour service access that is faster, easier and cheaper than conventional services with limited operating hours. Collaborate with the Farmers' Board of MojoLaban to help provide education on the definition and use of financial technology for farmers in financing, facilitation of transactions, financial planning and wealth processing. Fintech helps farmers with underbanked and unbanked categories because Fintec's assessment uses logarithms created by the creators of different applications from other conventional systems that require 5C conditions. (Capacity, Condition, Capital, Character dan Collateral). Socialization gives farmers a new understanding of the financial use of technology in Mojolaban district and knowledge of the benefits of using financial technology.